MODERASI BERAGAMA DI PAPUA: Rekonstruksi Identitas dan Resolusi Kehidupan Keagamaan Pasca Konflik Papua 1998-2001 - Luqman Al Hakim; Dudung Abdurahman (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This article analyzes the phenomenon of religious moderation in contemporary Papua. This problem is an interesting phenomenon, because since Papua became part of Indonesia in 1969, socio-religious developments in this region have often been colored by an atmosphere of disharmony between adherents of religions, and this atmosphere even contributed to the 1998-2001 Papuan conflict. However, after the conflict, religious moderation programs and counseling were carried out massively. This research seeks to reconstruct religious identity that supports the resolution of post-conflict religious life in Papua. This article focuses on the problem of why religious moderation occurs and what the implications are for religious life in Papua today. This research was conducted with a historical and socio-religious approach, as well as using historical research methods in which there are four stages, namely: heuristics, criticism, interpretation, and historiography. The findings of this study are: First, the 1998-2001 conflict in Papua was largely caused by a lack of nationalism and respect for fellow citizens. Second, post-conflict religious moderation efforts have been carried out by all religions and mass organizations in Papua. Religious leaders: Islam, Christianity, Hinduism, and Buddhism have played a role in the resolution and harmonization of religious life in Papua. Third, religious moderation in Papua greatly impacts social and spiritual aspects. Brotherhood in Papua does not look at religion, ethnicity, and culture, and issues surrounding an independent Papua are issues that undermine harmony in Papua.